Assesing the mediating effect of Self Control on the relationship betweeen Perceived Ease of Use of E-money on Consumptive Behavior and Internet Gaming Disorder of generation Z (Empirical Evidences from Indonesia) - Putra Tri Akram; Sita Deliyana Firmialy (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study was to determine how the mediating effect of self-control in the ease of using electronic money leads to consumptive behavior in internet gaming disorders. The world is currently experiencing rapid technological developments in all fields, including the gaming industry. This trend has resulted in more and more people focusing on the massive use of online games to distract them and focus, especially during the pandemic. The massive use of online games, or often referred to as internet gaming disorder (IGD), especially in Generation Z, has attracted many researchers around the world. Fast consumptive behavior and uncontrolled behavior are considered to bring harm to these online gamers. Furthermore, the integration of E-money in the game platform is expected to increase the flexibility of the consumptive behavior of these online gamers, thereby increasing the risk of IGD for these gamers. We used an online questionnaire that was tested on 155 respondents and thus analyzed the results by SEM-PLS. we found that ease of use e-money has a significant effect on consumptive behavior, self-control has an effect on ease of use of e-money, consumptive behavior has a significant effect on IGD. The empirical contribution of this study thus recommends the need to mediate control to these Generation Z gamers to suppress the tendency of rapid consumptive behavior and reduce the potential risk of developing Internet Gaming Disorder (emergency room)